Lactobacillus intestinalis facilitates tumor-derived CCL5 to recruit dendritic cell and suppress colorectal tumorigenesis - Yong Sun; Qiwen Wang; Yao Jiang; Jiamin He; Dingjiacheng Jia; Man Luo; Wentao Shen; Qingyi Wang; Yadong Qi; Yifeng Lin; Ying Zhang; Lan Wang; et al. (Gut Microbes)
Gut microbes play a crucial role in regulating the tumor microenvironment (TME) of colorectal cancer (CRC). Nevertheless, the deep mechanism between the microbiota-TME interaction has not been well explored. In this study, we for the first time discovered that Lactobacillus intestinalis (L. intestinalis) effectively suppressed tumor growth both in the AOM/DSS-induced CRC model and the ApcMin/+ spontaneous adenoma model. Our investigation revealed that L. intestinalis increased the infiltration of immune cells, particularly dendritic cells (DC), in the TME. Mechanically, the tumor-derived CCL5 induced by L. intestinalis recruited DC chemotaxis through the NOD1/NF-κB signaling pathway. In clinical samples and datasets, we found positive correlation between L. intestinalis, CCL5 level, and the DC-related genes. Our study provided a new strategy for microbial intervention for CRC and deepened the understanding of the interaction between tumor cells and the immune microenvironment modulated by gut microbes.